Приводы машин: Справочник - Длоугий В. В. Валентин Владимирович; Муха Т. И. Тамара Ивановна; Цупиков А. П. Анатолий Петрович; Януш Б. В. Борис Вячеславович (Ленинград, Машиностроение, 1982)
Авт. указаны на обороте тит. л.